MODEL BIOMIMETIC STUDIES OF TEMPLATED GROWTH AND ASSEMBLY OF NANOCRYSTALLINE FEOOH - Nesterova M.; Moreau J.; Banfield J.F. (My University, 2003)
We studied biomimetic mineralization of self-assembling polymer matrices in order to develop a model for biomineralization of iron oxides in nature. High-resolution transmission electron microscopy (HRTEM), rheology, and fluorescence probe analyses show self-assembly of acidic polysaccharide alginic acid (Alg) to form fibrils in dilute solutions. The resulting Alg fibrils are subsequently mineralized by FeOOH in a biomimetically controlled process. Experiments were conducted in pH 9.2 solutions containing millimolar concentrations of iron at 38°C. The unperturbed state of the hybrid mineral-organic structures was studied by characterization of samples of interfacial films collected from an inorganic-organic interface. Progress of mineralization over a 4-week period was followed by HRTEM, energy-dispersive X-ray analysis, and selected area electron diffraction. Morphologies of hybrid structures determined by HRTEM, X-ray powder diffraction, Fourier transform infrared spectroscopy, energy-dispersive X-ray analysis, and selected area electron diffraction suggest formation of iron (III) oxyhydroxide phases and their assembly through a variety of mechanisms, possibly occurring simultaneously. An initial step involves precipitation of nanometer-scale amorphous particles and two-line ferrihydrite in bulk solution. Some nanoparticles assemble into chains that recrystallize to form akaganeite (β-FeOOH), presumably via a solid-state transformation pathway. Small organic molecules may mediate this process by stabilizing the akaganeite structure and controlling particle assembly. Ferrihydrite particles also bind to acidic polysaccharide fibrils and are transformed to ordered arrays of akaganeite. The parallel orientation of adjacent akaganeite nanocrystals may be inherited from the orientation of precursor ferrihydrite, possibly conferred during attachment of ferrihydrite to the polyacid fibrils. Alternatively, particle-particle interactions may induce orientation, leading to recrystallization. Subsequently, akaganeite is transformed to goethite that is characterized by nanoscale porosity and fine-scale twinning on {021}. Dislocation, twin, and nanopore microstructures are consistent with coarsening by nanoparticle assembly, possibly templated by the substrate. Nanoparticle assembly to generate biomimetic hybrid materials may be relevant to formation of complex natural biominerals in natural systems where mineral nanoparticles, small organic molecules, and more complex polymers coexist.